Intelligenza artificiale e ortofoto per il censimento e la gestione delle aree pascolabili in ambiente alpino (GEOmedia, 2021)
Mountain areas include precious environmentslike pastures that require preservationstrategies by the appointed authorities. Herewe present a system that processes orthophotosacquired by Agenzia per le Erogazioni inAgricoltura using Artificial Intelligence to reducethe time and costs of human inspectionin pasture management activities. The systemis trained to automatically classify multiplekinds of pasture and no-pasture areas. A userinterface allows to query and refine the pasturemaps. The map can be updated as neworthophotos come in. The system achievesgood performance in the Provincia Autonomadi Trento (PAT), but it is suitable for similarmountain areas as well.